Couples' voluntary counselling and testing and nevirapine use in antenatal clinics in two African capitals: a prospective cohort study - Martha Conkling; Erin L Shutes; Etienne Karita; Elwyn Chomba; Amanda Tichacek; Moses Sinkala; Bellington Vwalika; Melissa Iwanowski; Susan A Allen (Journal of the International AIDS Society, 2010)
Background With the accessibility of prevention of mother to child transmission (PMTCT) services in sub‐Saharan Africa, more women are being tested for HIV in antenatal care settings. Involving partners in the counselling and testing process could help prevent horizontal and vertical transmission of HIV. This study was conducted to assess the feasibility of couples' voluntary counseling and testing (CVCT) in antenatal care and to measure compliance with PMTCT. Methods A prospective cohort study was conducted over eight months at two public antenatal clinics in Kigali, Rwanda, and Lusaka, Zambia. A convenience sample of 3625 pregnant women was enrolled. Of these, 1054 women were lost to follow up. The intervention consisted of same‐day individual voluntary counselling and testing (VCT) and weekend CVCT; HIV‐positive participants received nevirapine tablets. In Kigali, nevirapine syrup was provided in the labour and delivery ward; in Lusaka, nevirapine syrup was supplied in pre‐measured single‐dose syringes. The main outcome measures were nurse midwife‐recorded deliveries and reported nevirapine use. Results In eight months, 1940 women enrolled in Kigali (984 VCT, 956 CVCT) and 1685 women enrolled in Lusaka (1022 VCT, 663 CVCT). HIV prevalence was 14% in Kigali, and 27% in Lusaka. Loss to follow up was more common in Kigali than Lusaka (33% vs. 24%, p = 0.000). In Lusaka, HIV‐positive and HIV‐negative women had significantly different loss‐to‐follow‐up rates (30% vs. 22%, p = 0.002). CVCT was associated with reduced loss to follow up: in Kigali, 31% of couples versus 36% of women testing alone (p = 0.011); and in Lusaka, 22% of couples versus 25% of women testing alone (p = 0.137). Among HIV‐positive women with follow up, CVCT had no impact on nevirapine use (86‐89% in Kigali; 78‐79% in Lusaka). Conclusions Weekend CVCT, though new, was feasible in both capital cities. The beneficial impact of CVCT on loss to follow up was significant, while nevirapine compliance was similar in women tested alone or with their partners. Pre‐measured nevirapine syrup syringes provided flexibility to HIV‐positive mothers in Lusaka, but may have contributed to study loss to follow up. These two prevention interventions remain a challenge, with CVCT still operating without supportive government policy in Zambia.